Initial growth of Brachiaria subquadripara (Trin.) Hitchc. plants under different nutritional conditions - Vanessa D. Domingos; Dagoberto Martins; Neumarcio V. Costa; Andreia C. P. R. da Costa; Sidnei R. de Marchi (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the initial growth of emergent plants of Brachiaria subquadripara under different conditions of availability levels of the nutrients nitrogen (N), phosphorus (P), and potassium (K) provided to the plants via nutrient solution in a greenhouse. The treatments consisted of five concentrations of N (0, 42.0, 84.0, 126.0, and 168.0 mg L-1), five concentrations of P (0, 6.2, 12.4, 18.6, and 24.8 mg L-1) and five concentrations of K (0, 46.8, 93.6, 140.4, and 187.2 mg L-1) which were adapted from a base solution. The results showed that the initial growth of plants was slow up to 21 days after transplantation (DAT) and it increased in accordance with increments in N, P, and K concentrations in the nutrient solution up to the end of the study (35 DAT). The Relative Growth Rate and the Net Assimilation Rate of the B. subquadripara plants were larger when the N, P, and K concentrations were of 84.0, 18.6, and 46.8 mg L-1, respectively. These results suggest that this species can develop in environments considered hypereutrophic.